The relationship between service quality, customer satisfaction, and customer loyalty: A case study of a trading company in Mexico - Silva-Treviño, Juan Gilberto (Universidad Autónoma de Tamaulipas, 2021)
Service quality is considered an alternative for companies to obtain a competitive and sustainable advantage in a globalized economic environment. Small and medium-sized enterprises must offer a higher quality of service than large companies, and thus obtain customer preference. The objective of this study was to identify the relationship between service quality variable and the customer satisfaction and customer loyalty variables. Spearman’s correlation coefficient was used, and a statistical method based on exploratory factor analysis, aiming to extract the maximum variance of the data set within each factor. The results allowed observing a highly significant, positive, and strong correlation, with values of r = 0.820 and r = 0.803, between the variables of service quality, customer satisfaction, and customer loyalty. An important finding was the association between the tangible aspects dimension with the customer satisfaction and customer loyalty variables, with values of r = 0.910 and r = 0.919, respectively. On the other hand, in the factor analysis, through the explained total variance, it was observed that the eigenvalue is greater than 1 in the first five cases, where the percentage of the variance reaches a maximum value of 54.886 % in its first factor. Then, with five factors, 73.713 % of the variance of all the original data is explained. The study presented the limitation of its application in only one company. It was confirmed that, through better customer care and service, service quality constitutes an excellent tool for the profitability and sustainability of the organization.